2021
DOI: 10.1017/s0007114521001987
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietary intake of bioactive food compounds according to income level in the Brazilian population

Abstract: Background: There is an inverse association between bioactive compounds intake and disease risk. The knowledge of its consumption according to socioeconomic strata is important, which allows identification of potential intervention targets. Objective: To investigate bioactive compounds intake according to income level in Brazilian population. Design: Data were obtained from the Brazilian Household Budget Survey, a cross-sectional survey which included data on individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that socioeconomic status is an important determinant of differences in food intake, the intake of flavonoids increased with income level [ 20 , 36 , 37 ]. And in the high annual family income and the high PIR subgroup, we found that the negative association between LgTFs and TT4 became more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that socioeconomic status is an important determinant of differences in food intake, the intake of flavonoids increased with income level [ 20 , 36 , 37 ]. And in the high annual family income and the high PIR subgroup, we found that the negative association between LgTFs and TT4 became more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Developing epidemiological strategies to enrich foods with these compounds may constitute a public health strategy to reduce the risks of developing diseases like the ones mentioned above. In addition, dietary supplements enriched with polyphenols may be an effective way to increase consumption in the population, with favorable long-term results ( 16 , 87 , 88 ).…”
Section: The Molecular Structure and Role Of Polyphenolic Compounds F...mentioning
confidence: 99%
“…e bioactive compounds have therapeutic potential as well as an effect on energy intake, which reduces pro-inflammatory state, oxidative stress, and metabolic diseases [48]. Epidemiological information indicates intake of various kinds of foods that are rich in bioactive compounds and antioxidants such as vitamins, phytochemicals, and predominantly phenolic compounds such as flavonoids and carotenoids in high amount; shows its positive impact on health; and may help reduce the risk of various ailments, such as cancer, Alzheimer's, cataracts, heart disease, stroke, diabetes, and age-related functional degeneracy [49]. Bioactive compounds are competent to modulate metabolic processes that exhibit positive possessions such as inhibition of receptor activities, antioxidant effect, inhibition and induction of gene expression, and inhibition or induction of enzymes [50].…”
Section: Bioactive Compounds In Kodo and Little Milletsmentioning
confidence: 99%